Uncertainty and Financing Constraints - Bo, Hong; Lensink, Robert; Sterken, Elmer (Review of Finance, 2003)
Abstract Using a panel of Dutch listed firms this paper provides empirical evidence for the hypothesis that more risky firms are confronted with more severe capital market constraints than relatively less risky firms. The paper also contributes to the discussion on the usefulness of cash flow as a measure of financial constraints. We present a stochastic version of the Kaplan-Zingales (1997) model. We show that cash flow sensitivity can be used as a meaningful indicator of financing constraints if firms are classified by the degree of uncertainty they face and if the uncertainty originates from cost uncertainty. JEL classification codes: E22, G32.